Expressão gênica de células da córnea submetidas à infecção por acanthamoeba Spp - Sant'Ana, Viviane Peracini [UNIFESP] (2018)
Objective: The present research project proposes: 1) to analyze the proteolytic degradation of the main substrates present in the cornea (collagen, fibronectin, laminin and tubulin) with the Acanthamoeba exoproteome; 2) to analyze the cytotoxicity of the Acanthamoeba exoproteome of in HUVEC cells in 11 clinical isolates and which its main mechanism of induction of cell death; 3) to identify by benzamidinesepharose purification of the serine protease class; 4) to characterize the Acanthamoeba exoproteome at different pHs and temperatures; 5) to analyze the susceptibility of the Acanthamoeba exoproteome with diamidines and enzymatic inhibitors. Methods: Primary cultures of trophozoites were obtained by corneal scraping of patients with Acanthamoeba spp. Analysis of the Acanthamoeba exoproteome was performed by zymography (SDSPAGEgelatin), 0.01% gelatin polyacrylamide gel was prepared according to the subunits of its substrates: Fibronectin, Laminin and Tubulin. The HUVECs were cultured in a humid oven at 37 ° C to 5% CO2 in RPMI culture medium supplemented with 10% fetal bovine serum. The proteolysis assay of type I collagen was carried out by the hydrolysis of type I collagen, at a concentration of 0.4 mg / ml, previously dialyzed in specific buffer (50 mM TrisHCl, pH 7.5, 150 mM NaCl). In the analysis of the characterization of the Acanthamoeba exoproteome in different buffers of pHs and at different temperatures where each clinical isolate was removed from the gel and placed at different pHs (pHs 2.0 12.0). The diamidines used were 0.1% Brolene and 0.1% Désomédine, also 0.1 mM PMSF and 215 μM Trasylol enzyme inhibitors were used. Results: The proteolytic profile of Acanthamoeba exoproteome is associated with severity of infection observed in the patient. The degradation of type I collagen by the Acanthamoeba exoproteome the laboratory results corroborate with the clinical aspect observed in patients with moderate and severe amoebic keratitis. In the cytotoxicity assay, in vitro results from the Acanthamoeba exoproteome with HUVEC suggest the contact independence of trophozoite to induce cell death by apoptosis. We were able to demonstrate by in vitro protein assays, whose results prospect the mechanisms of gene expression in corneal cells, the functional aspects of different amoebic exoproteomes associated with healing and regeneration, whose processes are mainly mediated via cellular signaling in the host. Affinity chromatography demonstrated the prevalence of proteolytic enzymes of the class of serine proteases contained in the protozoan exoproteome. In the proteolysis assays of the Acanthamoeba exoproteome at different pH conditions and at different temperatures, it showed strong resistance to different pH and temperature conditions where they were evaluated in the period of 4 and 16 hours, where the optimum temperature was 35 ° C and 37 ° C in pH 7.0 appropriate conditions for the pathophysiology of amoebic keratitis. In the experiment with the diamidines, we noticed that unlike propamidine, hexamidine was not able to totally inhibit the enzymatic activity of the exoproteome. Conclusions: Exoproteome produced by Acanthamoeba spp trophozoites consists of a large diversity of enzymes, with emphasis on the enzymes belonging to the class of serine proteases. The enzymatic activity contained in the different amoebic exoproteomes suggests an important influence on the mechanisms of gene expression, with emphasis on the production of extracellular matrix compounds by corneal cells. The exoproteomes may present a pattern of physical and chemical resistance associated with enzymatic activity. The enzymatic constituents of different amoebic exoproteomes express proteins capable of degrading the main type I collagen and glycoproteins present in the cornea, besides inducing cell death by contact independent apoptosis. Laboratory isolation followed by amoebic exoproteome analysis demonstrates the importance of translational research associated with the present study, since the enzymatic constituents secreted by the protozoan can induce cell death and interferes in the synthesis of extracellular matrix compounds linked to the healing and regeneration processes tissue. Consequently, mechanisms associated with gene expression in epithelial cells and keratocytes can be inactivated, prospecting worsening in the clinical pattern of the patient.